Empowerment Public Branch Village 2 Amban District In Process Results Agriculture Sweet potato bitch Become processed Which Worth Economical And Highly Nutritious - Revisika Revisika; Wiska Baharuddin; Enik Maturahman (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2022)
Generally the farmers in the branch village 2 , Amban District, destination own results enough farming _ many of them is sweet potato creep , dive This This sweet potato only for sale raw and utilized as one _ food addition . Capabilities and skills possessed by farmers in process sweet potato bitch This in a manner general Not yet Not yet Lots so that activity planned training  important For done. Activity community service this is For practice farmer sweet potato in process sweet potato become processed worth economical and nutritious. Partner in activitiesa This is inhabitant the people of village 2 in the Amban district . The implementation of community service PKM uses the Participatory Rapid Appraisal (PRA) approach with the stages of activities, namely 1) planning, 2) implementation, and 3) evaluation. kindly general activity devotion done with Good with indicator participation partners during activity reached 100%, an increase understanding and skills reach 90% and response partners to activity training reach 100%. activity dedication This Still need done in a manner sustainable especially in packaging and marketing from the products that are produced